1990
DOI: 10.1161/01.atv.10.6.1045
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic high density lipoprotein binding proteins after administration of simvastatin and cholestyramine to rats.

Abstract: We investigated the regulation of putative high density lipoprotein (HDL) receptors in rat liver after cholesterol feeding and the administration of cholesterol-lowering drugs to rats. The expression of two plasma membrane HDL binding proteins (HB, and HB 2 ) were compared in control and treated livers by first separating membrane proteins on sodium dodecyl sulfate-polyacrylamide gels and quantitating HB, and HB 2 levels with a specific ligand blot assay. Of the various treatments used, only simvastatin or sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…This suggests some association, either direct or indirect, between HB 2 and cholesterol metabolism. If, as expected, sterol synthesis was decreased in the cholesterolloaded cells, it would be consistent with a finding reported by this laboratory previously (23) that the administration of simvastatin to rats down-regulated HB 2 (and HB 1 ) expression by 50%. More studies are planned to investigate these relationships between HDL binding, HB 2 levels, and cell cholesterol metabolism.…”
Section: Fig 4 Expression Of Hb 2 In Monocytes and Macrophagessupporting
confidence: 92%
“…This suggests some association, either direct or indirect, between HB 2 and cholesterol metabolism. If, as expected, sterol synthesis was decreased in the cholesterolloaded cells, it would be consistent with a finding reported by this laboratory previously (23) that the administration of simvastatin to rats down-regulated HB 2 (and HB 1 ) expression by 50%. More studies are planned to investigate these relationships between HDL binding, HB 2 levels, and cell cholesterol metabolism.…”
Section: Fig 4 Expression Of Hb 2 In Monocytes and Macrophagessupporting
confidence: 92%
“…We previously reported the presence of two HDL-binding proteins (HB 1 and HB 2 ) in rat and human liver plasma membranes (5,6) and also showed that the expression of these candidate HDL-receptors could be reduced 50% by treating rats with the hyperlipidemic drug simvastatin (23). HB 2 levels could also be influenced by uploading macrophages with cholesterol (16), suggesting that this adhesion-type of HDL-binding protein may also be involved in cell lipid metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Oral bioavailability of simvastatin in rats was well established in previous studies. [38][39][40] Multiple subcutaneous injections of simvastatin administered in the week after fracture result in increased serum levels, cholesterol-lowering effects, and bone formation, but systemic levels and lipid-lowering effects decrease by 4 weeks. 41 The authors know of no study examining local simvastatin administration during tendon repair in rats, and systemic simvastatin levels are likely to be minimal at 4 and 8 weeks after repair.…”
Section: Limitationsmentioning
confidence: 99%